Channels, Margin and Profit Beef Cattle Marketing Agencies from Bone District To Makassar City - . Hastang; A. Asnawi (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2015)
This study aimed to determine the channel marketing types, margin and profit of beef cattle marketing agency from Bone Regency to Makassar. The population of the study covered all beef cattle marketing agencies of Bone Regency to Makassar. Determination of the samples was done by snowball sampling method. Data were collected through direct observation and interviews. Data were then analyzed descriptively. The results showed that there were two forms of beef cattle marketing channel from Bone District to Makassar, the first channel: farmers to traders and then to the inter-area merchant and next to the slaughterhouse businessman, the second channel: farmers to inter-regional traders and next businessmen to the slaughterhouse. The marketing agency that received the largest margin was the cattle traders on the second channel, followed by the inter area cattle traders in the first channel, and the lowest was for the collector. However, the marketing agency that got the most benefit was the collector traders, followed by the inter area traders of the second channel, and the lowest was for inter area traders of the channel I. The longer the beef cattle marketing channel, the greater the margin and profits. The margin and Profit of marketing channel I (two levels) were much greater than those of marketing channel II (one level).